Review of hemodynamics in direct aspiration thrombectomy for the treatment of acute ischemic stroke - Shi, Yubing; Yang, Hongyi; Dong, Jing; Barnes, Peter (Journal of Gandaki Medical College-Nepal, 2024)
Introduction: Acute ischemic stroke (AIS) is a common and lethal cerebral vascular disease. Early thrombus removal is crucial to the patient treatment and recovery. Clinical studies suggested that Direct Aspiration Thrombectomy (DAT) is a promising minimally invasive treatment option for AIS patients. It is necessary to summarize the hemodynamic studies about the DAT for further improvement of the technology. Methods: This paper reviewed the current in vitro and computer modelling studies of the hemodynamic response in the DAT, commenting on the merits and the deficiencies in the related research works reported in the literature. Results: Review of literature reveals that majority of current studies were focused on the comparison of the responses produced by using various suction systems on catheters of different calibers. For future technical improvement to facilitate clinical treatment, we suggest that further research to concentrate on more in-depth hemodynamic analysis of the DAT procedure, including replacement of the constant suction pressure with pulsatile suction pressure, comparison of contact aspiration and non-contact aspiration, and optimization of catheter tip design. Conclusions: This review summarized the concurrent technical development about the hemodynamic studies of the DAT technique and suggested directions for future improvement, which is helpful for the improvement of the AIS treatment planning and design optimization of next generation of interventional catheters.